Pentingnya Pola Asuh Anak terhadap Pencegahan Stunting Anak Usia Dini di Desa Mekar Mulia Kecamatan Tanah Jawa Kabupaten Simalungun - Alif Lailasari Saragih; Tommi Ardiansyah; Alfioni Saragi; Milla Rantika; Sriani Sriani (MODELING: Jurnal Program Studi PGMI, 2023)
Stunting can be said to be a problem related to malnutrition caused by insufficient protein and nutrition intake, where children will experience disturbances in development and growth, including their proper height. The research method used in this study is a qualitative method involving community service programs, namely students of the North Sumatra Islamic University Real Work Lecture (UIN-SU) Group 166 located in Mekar Mulia Village, Kec. Java Land, Kab. Simalungun, North Sumatra. In the process of collecting data, it is assisted by observations, interviews, socialization or counseling to the local community. The existence of supporting data such as reading sources from various references, books, and documents from previous studies that are closely related to this research. The results of this study prove that the stunting rate in Mekar Mulia Village, Kec. Java Land, Kab. Simalungun, North Sumatra is still classified as low and not many are exposed to stunting, but the community is expected, especially mothers who have children or toddlers to need sustainable stunting understanding and counseling.